Two new species of Sericosura Fry & Hedgpeth, 1969 (Arthropoda: Pycnogonida: Ammotheidae), and a reassessment of the genus - Bamber, Roger N. (Zootaxa, 2009)
During analysis of the benthic pycnogonid fauna of the Irish Sea collected by the HABMAP project, a specimen representing an hitherto undescribed species of the genus Sericosura was discovered, representing the shallowest record for the genus, and the first Atlantic record away from oceanic ridges. The new species, Sericosura conta, is more compact than the seven species previously described, and has a much shorter chelifore scape. It is the only species of Sericosura outside the Pacific Ocean to have a nine-articled palp. Three specimens of a second new species, Sericosura hedgpethi, were collected by NIWA from a cold-seep site on the Hikurangi Margin. This New Zealand species has a seven-articled palp, and, uniquely for the genus, is entirely without chelifora. The genus is reviewed, Ammothea verenae is reassigned to Sericosura, and an identification key to males and females of the nine known species is given.